Integrating Yoga into Academic Settings: Effects on Students' Emotional Regulation and Well-being - Riya Sharma,; Prof. Harishankar Singh, (The Bioscan, 2025)
This study investigates the impact of a structured school-based yoga program on Emotional Intelligence and psychological well-being among secondary school students. Against the backdrop of increasing stress, emotional dysregulation, and academic pressure in adolescence, the research explores how yoga—a holistic practice combining asanas (physical postures), pranayama (breath regulation), and dhyana (meditation)—can enhance students’ self-awareness, emotional regulation, and social competencies within an educational setting. Ninth-grade students from an urban co-educational institution were divided equally into experimental and control groups using purposive sampling. The experimental group underwent a three months yoga intervention during school hours, while both groups were assessed pre- and post-intervention using a standardized Emotional Intelligence Scale. Statistical analysis revealed that students who participated in the yoga program demonstrated significant improvements across all measured domains: understanding emotional, understanding motivation, empathy, and handling relationship. These outcomes align with previous empirical findings that underscore yoga’s effectiveness in promoting emotional resilience, cognitive control, and self-efficacy in youth. Furthermore, the study contributes to the growing body of evidence supporting yoga as a culturally relevant, cost-effective, and scalable intervention for integrating mental health promotion into educational curricula. The findings advocate for the inclusion of contemplative practices in school systems to support adolescent mental well-being and socio-emotional learning, particularly in contexts striving to harmonize modern education with traditional values.